2009
DOI: 10.1093/jpepsy/jsp108
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Familial Decision-Making Regarding Human Papillomavirus Vaccination

Abstract: Although primary prevention of cervical and other cancers is available for preadolescent and adolescent girls, rates of HPV vaccine uptake are low. Future interventions should target vaccine intent and physician/family communication as a means to increasing HPV vaccination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(82 citation statements)
references
References 90 publications
5
73
1
2
Order By: Relevance
“…The main barriers for the implementation of HPV vaccination were then thought to be the cost, insufficient knowledge of the women about cervical cancer and the benefits of immunization, and, in a lesser degree, concerns about the efficacy and safety of the vaccine [24][25][26][27][28][29]. However, more recent studies have reported low rates of vaccination, despite the implementation of HPV immunization programs from health care systems around the world [24,25,30].…”
Section: Discussionmentioning
confidence: 99%
“…The main barriers for the implementation of HPV vaccination were then thought to be the cost, insufficient knowledge of the women about cervical cancer and the benefits of immunization, and, in a lesser degree, concerns about the efficacy and safety of the vaccine [24][25][26][27][28][29]. However, more recent studies have reported low rates of vaccination, despite the implementation of HPV immunization programs from health care systems around the world [24,25,30].…”
Section: Discussionmentioning
confidence: 99%
“…97 In keeping with this finding, strong provider recommendation has been shown as a key factor in adolescent vaccination in numerous studies. [98][99][100][101][102][103][104][105][106][107] However, research demonstrates that physicians discuss some adolescent vaccines, particularly HPV, differently than others. 104,[108][109][110] Given this, recent research has begun to focus on provider interventions to train them to talk about all adolescent vaccines in a way that is more conducive to vaccine acceptance, and to use proven communication strategies such as motivational interviewing 111,112 when vaccine hesitancy is encountered.…”
Section: Providing Free Vaccines/financial Incentivesmentioning
confidence: 99%
“…6-12 Generally, parents and adolescents have similar HPV vaccine beliefs, 11,13,14 including their risk appraisals, which predict their vaccination intentions and behaviors. However, some beliefs affect parents' and adolescents' motivations differently: The promise of preventing cancer encourages parents, 15,16 while fear of needles or pain discourages adolescents 6,9,11,17 from seeking vaccination.…”
mentioning
confidence: 99%